2021
DOI: 10.3389/fimmu.2021.782448
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Priming of Bladder Cancer Cells With Decitabine Increases Cytotoxicity of Human EGFR and CD44v6 CAR Engineered T-Cells

Abstract: BackgroundTreatment of B-cell malignancies with CD19-directed chimeric antigen receptor (CAR) T-cells marked a new era in immunotherapy, which yet has to be successfully adopted to solid cancers. Epigenetic inhibitors of DNA methyltransferases (DNMTi) and histone deacetylases (HDACi) can induce broad changes in gene expression of malignant cells, thus making these inhibitors interesting combination partners for immunotherapeutic approaches.MethodsUrothelial carcinoma cell lines (UCC) and benign uroepithelial H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
1
15
0
Order By: Relevance
“…Interestingly, extending the C6 hinge by 80 additional amino acids (C7) was not possible, as we observed non-specific binding of C7-hinged CD19 and R12 CARs to AML-M4/M5 cell lines, similarly to what has been described for CARs containing CH 2 CH 3 hinges from human immunoglobulins. 14 Moreover, we recently demonstrated that our C6 hinge worked in CAR constructs recognizing solid tumor-associated antigens 49 , 50 and also here did not result in off-target activation of the genetically modified T cells, thus suggesting again that the C6 hinge seems to be well suited for CAR constructs for clinical products.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, extending the C6 hinge by 80 additional amino acids (C7) was not possible, as we observed non-specific binding of C7-hinged CD19 and R12 CARs to AML-M4/M5 cell lines, similarly to what has been described for CARs containing CH 2 CH 3 hinges from human immunoglobulins. 14 Moreover, we recently demonstrated that our C6 hinge worked in CAR constructs recognizing solid tumor-associated antigens 49 , 50 and also here did not result in off-target activation of the genetically modified T cells, thus suggesting again that the C6 hinge seems to be well suited for CAR constructs for clinical products.…”
Section: Discussionsupporting
confidence: 59%
“…After the establishment of an optimized transduction protocol, primary human NK cells with low CD33 expression were transduced with 5-fold concentrated BaEV-Rless-pseudotyped lentiviral particles encoding BFP in cis with CD19, CD33, CD123, or EGFR CARs, harboring our CD34-derived hinge ( 20 , 29 ), on Retronectin ( Figures 2A, B ). Three to four days after transduction, the expression of the CARs was analyzed after staining of the C6 hinge region with the QBend-10 antibody and detecting BFP expression by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of CAR immune effector cells to eliminate their target cells is influenced by several factors, including the affinity of the scFv present in the CAR construct, the expression levels of the CAR itself on the effector cells, and availability of the targeted antigen/epitope on the target cell ( 8 , 29 ). Thus, for CARs with a low affinity or when the target antigen is expressed at low levels, high and stable CAR expression is crucial to ensure excellent antitumor cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vesicular stomatitis virus G glycoprotein-pseudotyped replication-deficient lentiviral vectors were generated by polyethyleneiminie transfection (Sigma-Aldrich, Darmstadt, Germany) of 6 μg pczVSV-G, 6 μg pCD-NL/BH, and 6 μg vector plasmid into HEK293T cells as described previously. 24 , 62 , 63 Two days after transfection, virus-containing supernatant was harvested, filtered (0.45 μm), and used for transduction of eukaryotic cells. For the transduction of Jurkat or primary human T cells, 5 × 10 5 cells were incubated with 2 mL virus-containing supernatant and 10 μg/mL protamine phosphate (Sigma-Aldrich) for 24 h, replenished with fresh medium, and used for experiments after 48 h.…”
Section: Methodsmentioning
confidence: 99%